2009
DOI: 10.1002/lt.21651
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and employment status of liver transplant patients

Abstract: Health-related quality of life (HRQoL) is one preferable outcome measure of medical interventions such as liver transplantation (LT). The aim of this study was to compare HRQoL of LT patients with that of the general population and to assess the employment status of LT patients. HRQoL was measured with the 15D instrument, a validated, nondisease-specific, 15-dimensional, self-administered HRQoL instrument. The questionnaire was sent to all adult LT patients in Finland (401 patients) alive in June 2007. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 28 publications
(52 reference statements)
14
70
0
3
Order By: Relevance
“…This difference was pronounced in the psychological and social domains of HRQoL. The relationship between having a job and a better perceived HRQoL was also found in previous studies in the general population43, 44 and other patient populations 45, 46. Employment is important to the patients, as it provides them with an income, opportunities to structure their daily lives, and satisfying social interactions, all of which can affect HRQoL.…”
Section: Discussionsupporting
confidence: 64%
“…This difference was pronounced in the psychological and social domains of HRQoL. The relationship between having a job and a better perceived HRQoL was also found in previous studies in the general population43, 44 and other patient populations 45, 46. Employment is important to the patients, as it provides them with an income, opportunities to structure their daily lives, and satisfying social interactions, all of which can affect HRQoL.…”
Section: Discussionsupporting
confidence: 64%
“…The finding of the current study may be due to; the average age of the studied subjects was 50 years. [19] This was in the same line with the study done by Saab et al, (2007) at University of California, who stated that, the ability of liver transplant clients to return to their daily activities including employment is controversial and the most important factors affecting employment include age at time of transplantation, duration of disability prior to transplantation, and physical/general health performance status. [32] From the researcher point of view return to active and productive life is a key goal of current liver transplantation.…”
Section: Discussionsupporting
confidence: 62%
“…The authors found that among 347 respondents, a third of all patients was employed during the study period, without differences depending on the etiology of indication. Among respondents of working age (20-65 years old), with n = 268, 44% were active and these had better QOL than unemployed respondents of working age, with clinically important and statistically significant difference (p <0.0001) (24) . The predominant income of the study participants was considered low because most received up to two minimum wages (43.3%) and three to four (25.3%), totaling 68.5% of the sample.…”
Section: Discussionmentioning
confidence: 95%